Infection of male rats with Toxoplasma gondii results in enhanced delay aversion and neural changes in the nucleus accumbens core - Tan, Donna (Proc Biol Sci, 2015)
Rats infected with the protozoan parasite Toxoplasma gondii exhibit reduced avoidance of predator odours. This behavioural change is likely to increase transmission of the parasite from rats to cats. Here, we show that infection with T. gondii increases the propensity of the infected rats to make more impulsive choices, manifested as delay aversion in an intertemporal choice task. Concomitantly, T. gondii infection causes reduction in dopamine content and neuronal spine density of the nucleus accumbens core, but not of the nucleus accumbens shell. These results are consistent with a role of the nucleus accumbens dopaminergic system in mediation of choice impulsivity and goal-directed behaviours. Our observations suggest that T. gondii infection in rats causes a syndromic shift in related behavioural constructs of innate aversion and making foraging decisions.